Centralized red muscle in Odontaspis ferox and the prevalence of regional endothermy in sharks ... : العضلة الحمراء المركزية في Odontaspis ferox وانتشار ماص الحرارة الإقليمي في أسماك القرش ... - Haley R. Dolton; Edward P. Snelling; Robert Deaville; Andrew L. Jackson; Matthew W. Perkins; Jenny R. Bortoluzzi; Kevin Purves; David J. Curnick; Catalina Pimiento; Nicholas L. Payne (OpenAlex, 2023)
The order Lamniformes contains charismatic species such as the white shark Carcharodon carcharias and extinct megatooth shark Otodus megalodon , and is of particular interest given their influence on marine ecosystems, and because some members exhibit regional endothermy. However, there remains significant debate surrounding the prevalence and evolutionary origin of regional endothermy in the order, and therefore the development of phenomena such as gigantism and filter-feeding in sharks generally. Here we show a basal lamniform shark, the smalltooth sand tiger shark Odontaspis ferox , has centralized skeletal red muscle and a thick compact-walled ventricle; anatomical features generally consistent with regionally endothermy. This result, together with the recent discovery of probable red muscle endothermy in filter feeding basking sharks Cetorhinus maximus , suggests that this thermophysiology is more prevalent in the Lamniformes than previously thought, which in turn has implications for understanding the ... : يحتوي ترتيب Lamniformes على أنواع كاريزمية مثل القرش الأبيض Carcharodon carcharias والقرش العملاق المنقرض Otodus megalodon ، وهو ذو أهمية خاصة نظرًا لتأثيره على النظم الإيكولوجية البحرية، ولأن بعض الأعضاء يظهرون ماصًا إقليميًا للحرارة. ومع ذلك، لا يزال هناك جدل كبير حول الانتشار والأصل التطوري لمادة ماصّة للحرارة الإقليمية بالترتيب، وبالتالي تطور ظواهر مثل العملاقة والتغذية بالفلتر في أسماك القرش بشكل عام. هنا نعرض سمكة قرش صفائحية قاعدية، سمكة قرش النمر الرملي ذات الأسنان الصغيرة Odontaspis ferox ، لديها عضلة حمراء هيكلية مركزية وبطين سميك مضغوط الجدران ؛ السمات التشريحية متسقة بشكل عام مع ماص للحرارة إقليميا. تشير هذه النتيجة، جنبًا إلى جنب مع الاكتشاف الأخير لباطن الحرارة المحتمل للعضلات الحمراء في أسماك القرش المتشمسة للفلتر Cetorhinus maximus ، إلى أن هذه الفيزيولوجيا الحرارية أكثر انتشارًا في Lamniformes مما كان يعتقد سابقًا، والتي بدورها لها آثار على فهم تطور باطن الحرارة الإقليمي، والعملقة، وخطر انقراض أنواع أسماك القرش ذات الأجسام الدافئة في الماضي والحاضر. ...